Tumor inhibition by sodium selenite is associated with activation of c-Jun NH2-terminal kinase 1 and suppression of β-catenin signaling - Fang, Wenfeng (2010)
Epidemiological and clinical studies suggest that an increased intake of dietary selenium significantly reduces overall cancer risk, but the anti-cancer mechanism of selenium is not clear. In the present study, we fed intestinal cancer mouse model Muc2/p21 double mutant mice with a selenium-enriched (sodium selenite) diet for 12 weeks or 24 weeks, and found that sodium selenite significantly inhibited intestinal tumor formation in these animals (p<0.01), which was associated with phosphorylation of JNK1 and suppression of β-catenin and COX2. In vitro studies showed that sodium selenite promoted cell apoptosis and inhibited cell proliferation in human colon cancer cell lines HCT116 and SW620. These effects were dose- and time course- dependent, and were also linked to an increase of JNK1 phosphorylation and suppression of β-catenin signaling. Reduced JNK1 expression by small RNA interference abrogated sufficient activation of JNK1 by sodium selenite, leading to reduced inhibition of the β-catenin signaling, resulting in reduced efficacy of inhibiting cell proliferation. Taken together, our data demonstrate that sodium selenite inhibits intestinal carcinogenesis in vivo and in vitro through activating JNK1 and suppressing β-catenin signaling, a novel anti-cancer mechanism of selenium.